A review of fish-handling training activities in Malaita Province - Batalofo, Margaret; Hunnam, Kimberly; Buga, Ben; Jasper, Martin; Isihanua, Mathew; Eriksson, Hampus (WorldFish, 2023)
In Solomon Islands, many fishers, fish vendors and processors live and work in remote locations without access to electricity, roads, clean water or landing-site facilities. Some may also lack the skills, knowledge or capital to invest in new equipment or put their ideas into practice. As a result, fish is often handled in ways that cause spoilage or contamination with dirt or bacteria, which can reduce income earned and make consumers sick or hesitant to eat fish. While there are many factors that contribute to poor fish-handling practices, provision of training to increase knowledge, develop skills and change attitudes is one step that can be taken to improve the quality of fishery products. In some provinces, including Malaita Province, several training workshops on fish handling have been held in the past for both fishers and fish vendors. However, to our knowledge, there has been no evaluation of such workshops to understand their effectiveness in bringing about change.